Ethanol foam: a novel type of foam sclerosant for treating venous malformations - Zhang, Han-Shu; Liu, Yi-Ran; Liu, Shao-Hua (Frontiers in Neurology, 2024)
Introduction Sclerotherapy is a commonly utilized treatment approach for venous malformations. Absolute ethanol is renowned for its remarkable efficacy as a potent sclerosants, but it is potentially associated with severe complications. Foam sclerotherapy is considered superior to liquid sclerotherapy owing to its heightened efficacy and diminished incidence of complications. Thus, our objective was to devise an ethanol foam sclerosant that delivers exceptional efficacy while mitigating complications. Methods In the first set of experiments, we identified the suitable range of ethanol concentrations for sclerotherapy through human umbilical vein endothelial cell proliferation assays and blood clotting experiments. Next, the surfactants polysorbate 80, egg yolk lecithin, and hyaluronic acid were added to create stable ethanol foam, with their ratios meticulously optimized. Results The optimal concentration range of ethanol was determined to be 30–60%. Eventually, a 48% ethanol foam was successfully produced with excellent stability. Other than ethanol, the formulation included 5 × 10−3 g/mL polysorbate 80, 10−2 g/mL egg yolk lecithin, and 0.04 mL/mL hyaluronic acid. Discussion The novel ethanol foam produced here could be a promising candidate for the treatment of venous malformations.